The political economy reader: markets as institutions - Barma, Naazneen; Barma, Naazneen H.; Vogel, Steven Kent (Routledge, 2007)
This reader combines in a single volume the key writings of classical and contemporary thinkers on political economy. The articles provide both a theoretical approach to understanding capitalism and a survey of the varieties of capitalism around the world today, examining the interaction between politics and markets both in theory and practice. Drawing on history, economics, political science and sociology, it emphasizes the ways in which markets are embedded in and influenced by political and social institutions. Steven K. Vogel and Nazneen Haider Barma provide an informative overview of a number of the most significant controversies and contemporary debates in political economy through the selections of contending perspectives on a variety of issues, including: How can rich countries make their economies more competitive? How can poor countries achieve economic development? How can post-communist countries make a successful transition to markets? Will theinformation technology revolution render the national varieties of capitalism obsolete? Does globalization imply that the national varieties of capitalism will converge to one global capitalism? A Political Economy Reader will be an essential resource for students of political economy and economic sociology.
Political Science; Sociology
Keywords: business & economics; capitalism; economics; international economic relations; political economy; political science; sociology

Against the Law: Labor Protests in China’s Rustbelt and Sunbelt - Lee, Ching Kwan (University of California Press, 2007)
This study opens a critical perspective on the slow death of socialism and the rebirth of capitalism in the world's most dynamic and populous country. Based on remarkable fieldwork and extensive interviews in Chinese textile, apparel, machinery, and household appliance factories, Against the Law finds a rising tide of labor unrest mostly hidden from the world's attention. Providing a broad political and economic analysis of this labor struggle together with fine-grained ethnographic detail, the book portrays the Chinese working class as workers' stories unfold in bankrupt state factories and global sweatshops, in crowded dormitories and remote villages, at street protests as well as in quiet disenchantment with the corrupt officialdom and the fledgling legal system.
Anthropology
Keywords: China; cultural anthropology; double movement; fictitious commodities; labour; social anthropology

The Transnational Politics of Corporate Governance Regulation - Overbeek, Henk; Apeldoorn, Bastiaan van; Nölke, Andreas (Routledge, 2007)
This ambitious volume explores the politics of recent changes in corporate governance regulation and the transnational forces driving the process. Corporate governance has in the 1990s become a catchphrase of the global business community. The Enron collapse and other recent corporate scandals, as well as growing worries in Europe about the rise of Anglo-Saxon finance, have made issues of corporate governance the subject of political controversies and of public debate. The contributors argue that the regulation of corporate governance is an inherently political affair. Given the context of the deepening globalization of the corporate world, it is also increasingly a transnational phenomenon. In terms of the content of regulation the book shows an increasing reliance on the application of market mechanisms and a tendency for corporations themselves to become commodities. The emerging new mode of regulation is characterized by increasing informalization and by forms of private regulation. These changes in content and mode are driven by transnational actors, first of all the owners of internationally mobile financial capital and their functionaries such as coordination service firms, as well as by key public international agencies such as the European Commission. The Transnational Politics of Corporate Governance Regulation will be of interest to students and researchers of international political economy, politics, economics and corporate governance.
Political Science
Keywords: NGOs; NGOs (non-governmental organizations); business & economics; economic policy; international political economy; political science; public policy

Reading Karl Polanyi for the Twenty-First Century - Bugra, A. (Palgrave Macmillan, 2007)
Using Karl Polanyi's analysis of the separation of politics and the economy, the book argues that the market economy is not a spontaneous process, but a...
Economics; Sociology
Keywords: commodification; financial economics; macroeconomics; market economy; monetary economics

Third Ways: How Bulgarian Greens, Swedish Housewives, and Beer-swilling Englishmen Created Family-centered Economies– and why They Disappeared - Carlson, Allan C. (ISI Books, 2007)
Freewheeling capitalism or collectivist communism: when it came to political-economic systems, did the twentieth century present any other choice? Does our century? In Third Ways, social historian Allan Carlson tells the story of how different thinkers from Bulgaria to Great Britain created economic systems during the twentieth century that were by intent neither capitalist nor communist. Unlike fascists, these seekers were committed to democracy and pluralism. Unlike liberal capitalists, they refused to treat human labor and relationships as commodities like any other. And unlike communists, they strongly defended private property and the dignity of persons and families. Instead, the builders of these alternative economic systems wanted to protect and renew the “natural” communities of family, village, neighborhood, and parish. They treasured rural culture and family farming and defended traditional sex roles and vital home economies. Carlson's book takes a fresh look at distributism, the controversial economic project of Hilaire Belloc and G. K. Chesterton which focused on broad property ownership and small-scale production; recovers the forgotten thought of Alexander Chayanov, a Russian economist who put forth a theory of “the natural family economy”; discusses the remarkable “third way” policies of peasant-led governments in post–World War I Bulgaria, Poland, and Romania; recounts the dramatic and largely unknown effort by Swedish housewives to defend their homes against radical feminism; relates the iconoclastic ideas of economic historian Karl Polanyi, including his concepts of “the economy without markets” and “the great transformation”; and praises the efforts by European Christian Democrats to build a moral economy on the concept of homo religious—“religious man.” Finally, Carlson's work explains why these efforts—at times rich in hope and prospects—ultimately failed, often with tragic results. The tale inspires wistful regret over lost opportunities that, if seized, might have spared tens of millions of lives and forestalled or avoided the blights of fascism, Stalinism, socialism, and the advent of the servile state. And yet the book closes with hope, enunciating a set of principles that could be used today for invigorating a “family way” economy compatible with an authentic, healthy, and humane culture of enterprise.
History; Economics
Keywords: business & economics; economic history; economic theory; economics / comparative; history - modern; history / 20th Century

Beyond the boycott: labor rights, human rights, and transnational activism - Seidman, G. (Russell Sage Foundation, 2007)
Sociology
Keywords: business & economics - international; business & economics / business ethics; law / labor & employment; political science / human rights; political science / labor & industrial relations; political science / labour & industrial relations; social science - developing and emerging countries; social science / sociology / general